Development of 4D Model-Based Mathematics Teaching Materials on Geometry to Improve Learning Outcomes of Islamic Elementary School (MI) Students - Erna Puji Astuti; Minnah El Widdah; Heroza Firdaus (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The purpose of this research is to enhance the mathematical knowledge of fifth graders at Jambi City's Ibtidaiyah Nurul Ihsan College by creating lesson plans that focus on geometrical concepts. There were four phases to the Research and Development (R&D) process that were used in this study: define, design, development, and disseminate. A total of twenty-two fifth graders served as the research subjects. Interviews, surveys, and tests were used to gather information, and both quantitative and qualitative methods were used to analyse it. Based on assessments by language experts, subject matter experts, and tool experts, the created instructional materials showed extremely high validity. Feedback from both instructors and students indicated that the materials were useful in enhancing students' grasp of geometric concepts. Therefore, the created maths lessons are a good substitute for traditional textbooks since they help primary school students learn mathematics in a way that is more interesting, dynamic, and accessible.